The Implementation of Science, Technology and Society Environment (STSE)-Based Learning for Developing Pre-Service General Science Teachers’ Understanding of the Nature of Science by Empirical Evidence - Gathong, S.; Chamrat, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
The objective of this research was to study the outcomes of teaching method based on Science, Technology, Society, and Environment (STSE) in enhancing the nature of science understanding, emphasizing the empirical evidence among 23 pre-service general science teachers at one of Rajabhat Universities in the upper northern region, Thailand. The samples were selected using the purposive random sampling technique from a population of bachelor education program students who enrolled in the second semester in the academic year of 2016. The research instruments consisted of questionnaires and ten learning management plans based on the concept of Science, Technology, Society, and Environment (STSE) emphasizing on empirical evidence covering ten environmental issues in the upper northern region. Such learning managements have steps for students to utilize empirical evidence to create the nature of science understanding.Ã‚Â Mean and standard deviation were applied to data analysis, then the results were presented descriptively. The research found that the pre-service teachers had a better understanding of the nature of science after studying with the statistical significance and were satisfied with the implementation of the teaching method.